C-terminal domain on the outer surface of the Macrobrachium rosenbergii nodavirus capsid is required for Sf9 cell binding and internalization - Monsicha Somrit (2018)
© 2016 Elsevier B.V. We have shown that Macrobrachium rosenbergii nodavirus (MrNV) was able to infect Sf9 cells and that MrNV virus-like particles (MrNV-VLPs) were capable nanocontainers for delivering nucleic acid-based materials. Here, we demonstrated that chymotryptic removal of a C-terminal peptide and its truncated variant (F344-MrNV-VLPs) exhibited a drastically reduced ability to interact and internalize into Sf9 cells. Electron microscopic observations revealed that the loss of C-terminal domain either from enzyme hydrolysis or genetic truncation did not affect the generated MrNV-VLPs’ icosahedral conformation, but did drastically affect the VLPs’ internalization ability into Sf9 cells. Homology-based modelling of the MrNV capsid with other icosahedral capsid models revealed that this chymotrypsin-sensitive C-terminal domain was not only exposed on the capsid surface, but also constituted the core of the viral capsid protrusion. These results therefore suggest the importance of the C-terminal domain as a structure for targeted cell interaction which is presumably localized at the protruding domain. This work thus provided the functional insights into the role of the MrNV C-terminal domain in viral entry into Sf9 cells and lead to the development of strategies in combatting MrNV infection in susceptible cells.